Tri-state Space Vector Modulation for Three-phase integrated inverters - Galotto, L. [UNESP]; Godoy, R. B.; De Brito, Moacyr A. G. [UNESP]; Garcia, R. C.; Kimpara, M. L M; Canesin, Carlos A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2011)
The aim of this work is to present a modified Space Vector Modulation (SVM) suitable for Tri-state Three-phase inverters. A standard SVM algorithm and the Tri-state PWM (Pulse Width Modulation) are presented and their concept are mixed into the novel SVM. The proposed SVM is applied to a three-phase tri-state integrated Boost inverter, intended to Photovoltaic Energy Applications. The main features for this novel SVM are validated through simulations and also by experimental tests. The obtained results prove the feasibility of the proposal. © 2011 IEEE.
Keywords: Integrated Inverters; Photovoltaic Energy Applications; Space-Vector Modulation; Tri-State Modulation; Boost inverters; Experimental test; Integrated inverter; Photovoltaic energy; Space Vector Modulation; SVM algorithm; Three-phase inverter; Integration; Modulation; Photovoltaic effects; Power electronics; Pulse width modulation; Vector spaces